Evidence for Cultured Human Vascular Smooth Muscle Cell Heterogeneity: Isolation of Clonal Cells and Study of their Growth Characteristics - Benzakour, Omar; Kanthou, Chryso; Kanse, Sandip M; Scully, Michael F; Kakkar, Vijay V; Cooper, David N (Thrombosis and Haemostasis, 1996)
The monoclonal theory of atherosclerosis postulates that the initial vascular smooth muscle cell (VSMC) proliferative event involves the expansion of a single cell or a sub-population of cells thus implying differences in the replicative potential of VSMC. Using the technique of limited dilution, VSMC clones derived from animal tissues have been previously isolated and shown to be morphologically heterogeneous. However, the same technique applied to human VSMC (HVSMC) has been unsuccessful, possibly because HVSMC do not grow when plated at very low densities. In this report, the anchorage-independent growth of HVSMC in semi-solid medium was studied. Platelet-derived growth factor-BB (PDGF-BB) and to a lesser extent PDGF-AB and basic fibroblast growth factor (bFGF) induced colony formation. This assay provided a tool for the isolation of HVSMC clones. In terms of their growth characteristics and responsiveness to several growth factors, isolated HVSMC clones and the original parental cell population exhibited marked heterogeneity.